FEATURES OF DEVELOPMENT OF THE TECHNOLOGY OF DIGITAL TRANSFORMATION IN RUSSIA - S. A. Inozemtseva (Современная наука и инновации)
Fast, accessible and complete acquisition of the necessary information for making any kind of decisions is relevant in any branch of the industry